Three new species of Myxosporea (Bivalvulida: Ceratomyxidae: Alatasporidae) from the gall bladders of anglerfishes Lophius spp. (Teleostei: Lophiidae) in the Northeast Atlantic Ocean - Afonso-Dias, Isabel; Kalavati, Chaganti; Mackenzie, Ken; Mackenzie, Kevin S. (Zootaxa, 2007)
Three new species of myxosporeans are described from the gall bladders of Lophius piscatorius L. and L. budegassa Spinola. Ceratomyxa lophii n. sp. was found in 14 of 42 L. piscatorius from two locations to the northwest of Scotland in March 2000. Alataspora budegassai n. sp. was found in all eight specimens of L. budegassa caught off Algarve in the south of Portugal in June and August 2000. Pseudalataspora lophii n. sp. was found in 21 of 48 L. piscatorius from six locations to the west and northwest of Scotland in March 2000, March 2004 and October 2004. Ceratomyxa lophii n. sp. is one of only a few species of the genus having unequal spore valves, but differs from all the other species in spore dimensions and in the form of the plasmodium. The dimensions of the spore of Alataspora budegassai n. sp. are very similar to those of A. africana Shulman, Kovaleva & Dubina, 1979, described from a species of perciform fish caught off West Africa, but are markedly different from those of any of the other 15 described species of Alataspora. Pseudalataspora lophii n. sp. differs from the other 11 species of Pseudalataspora described to date in the dimensions of the spore and other features.